Comprehensive estimates of seabird–fishery interactions for the US Northeast and mid‐Atlantic. Issue 1 (10th August 2017) - Hatch, Joshua M.
Abstract: Relatively little is known about seabird–fishery interactions (i.e. bycatch) for the U.S. North‐east and mid‐Atlantic, despite concerted efforts to document observed interactions since 1989. Fisheries observer data were used to estimate seabird–fishery interactions for 10 species and six gear types that operated within the US Northeast and mid‐Atlantic from 1996 to 2014. Hierarchical Bayes estimation was used and accounted for temporal, spatial, and operational considerations inherent in the data through post‐stratification. Over the 19‐year study period, 48 821 (coefficient of variation [CV] = 0.03) seabirds were estimated to have interacted with commercial fishing gear, resulting in an average of 2570 interactions per year. Trends in estimated interactions were explored using the marginal posterior distributions, with the majority of interactions pertaining to gillnets and shearwaters/fulmars. Comparison with previous work highlighted the need for consistency in data preparation, making it easier to compare relative trends in seabird bycatch estimates for the region. Future assessments should focus on providing context for the interaction estimates, so that population‐level impacts can be inferred and the necessary conservation measures enacted.